This preview shows page 1. Sign up to view the full content.
Unformatted text preview: with axiom A1, i.e such that A 1 = A 1. 2. Use results from QUESTION 3 to determine whether | = K A 3 . 3. Write a formal proof A 1 ,A 2 in S from the QUESTION 3 with 1 application of the rule ( r ) that starts with axiom A2, i.e such that A 1 = A 2. 4. Use results from QUESTION 1 to determine whether | = A 2 . QUESTION 3 Prove, by constructing a formal proof in S from the QUESTION 1 that S ( A ( A ( A ( A A )))) . 1...
View Full Document
- Spring '08
- Computer Science